Patients' Experiences with Cancer Care: Impact of the COVID-19 Pandemic. (April 2022) - Treiman, Katherine; Kranzler, Elissa C.; Moultrie, Rebecca; Arena, Laura; Mack, Nicole; Fortune, Erica; Garcia, Reese; Street, Richard L
The COVID-19 pandemic heightened the psychosocial impact of a cancer diagnosis as patients face concerns about the risk of infection and serious disease and uncertainties about the impact on their treatment. We conducted an online survey (n = 317) and focus groups (n = 19) with patients to examine their experiences with cancer care during the pandemic. Most survey respondents (68%) reported one or more disruptions or delays in care, including appointments switched to telehealth (49%). Patients perceived both benefits (e.g., convenience) and drawbacks (e.g., more impersonal) to telehealth. For many patients, COVID-19-related restrictions on bringing family members to support them during appointments was a major concern and left them feeling alone and vulnerable during treatment. Patients' self-reported coping during the pandemic was positively associated with age, education, and income ( P < .05 for each) and better communication with their doctors during telehealth sessions ( P < .001). Study findings highlight the importance of patient-centered care and communication to help patients cope with the challenges of the pandemic. Further research is needed to develop guidelines for use of telehealth as part of patient-centered cancer care.